2006
DOI: 10.34194/geusb.v11.4931
|View full text |Cite
|
Sign up to set email alerts
|

Faults and fractures in central West Greenland: onshore expression of continental break-up and sea-floor spreading in the Labrador – Baffin Bay Sea

Abstract: The complex Ungava fault zone lies in the Davis Strait and separates failed spreading centres in the Labrador Sea and Baffin Bay. This study focuses on coastal exposures east of the fault-bound Sisimiut basin, where the onshore expressions of these fault systems and the influence of pre-existing basement are examined. Regional lineament studies identify five main systems: N–S, NNE–SSW, ENE–WSW, ESE–WNW and NNW–SSE. Field studies reveal that strike-slip movements predominate, and are consistent with a ~NNE–SSW-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(57 citation statements)
references
References 25 publications
0
57
0
Order By: Relevance
“…). Here, the cause of this changing distribution is considered, alongside the relationship of the offshore structures and those previously published from onshore (Japsen et al ., ; Wilson et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…). Here, the cause of this changing distribution is considered, alongside the relationship of the offshore structures and those previously published from onshore (Japsen et al ., ; Wilson et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…In particular, on Line G it appears that the ITZ may correspond to the bounding fault of the basin shown on this line as the approximate continuation of the ITZ would be expected here, the dip direction of the basin bounding fault is similar and the reflection characteristics of the basement either side of this structure are what would be expected based on the onshore geology, i.e. the folded fabrics of the CNO and SNO display different internal reflectivity compared to within the ITZ (Wilson et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The Palaeoproterozoic Nagssugtoqidian orogenic belt to the north of the North Atlantic Craton was first identified as a persistent (>2.5 Gyr) tectonic lineament by Watterson (1975), who regarded the boundary as a lithosphere-scale structure due to the presence of Cambrian age kimberlites that are crosscut by Mesozoic age pseudotachylytes (Grocott, 1977). Subsequent investigation of brittle deformation in exposures of the Nagssugtoqidian Orogen adjacent to the Davis Strait by Wilson et al (2006) revealed a two-phase model for fault development that is compatible with the development of the Mesozoic to Cenozoic continental margin offshore (Chalmers et al, 1993;Oakey & Chalmers, 2012). Wilson et al (2006) found that the Phase 1 generally N-S trending normal faults were kinematically compatible with the early NW-SE opening of the Labrador Sea-Davis Strait-Baffin Bay seaway in the Cretaceous to Paleocene.…”
Section: The Influence Of the Mantle Lithosphere In Tectonic Processesmentioning
confidence: 99%